Examining the impact of service quality and product innovation on willingness to buy electric vehicles: the mediating role of customer satisfaction - Sitinjak Charli; Ober Józef (Production Engineering Archives)
Adopting electric vehicles (EVs) is a critical step towards achieving sustainable and environmentally friendly transportation systems in urban areas. This study delves into the factors that influence consumers’ willingness to buy electric vehicles in Jakarta, Indonesia, focussing on the mediating role of customer satisfaction. The research framework integrates service quality, product innovation, and customer satisfaction as key determinants of the adoption of electric vehicles. Data from 420 respondents were analysed using regression and mediation analyses. The findings underscore the importance of service quality and product innovation in shaping consumers’ willingness to embrace EVs. Efficient after-sales services, responsive customer support, and innovative product features positively impact consumers’ perceptions and willingness to adopt electric vehicles. Furthermore, customer satisfaction emerged as a crucial mediator in this process, highlighting the importance of ensuring ongoing satisfaction throughout the EV ownership experience. These insights offer valuable guidance to EV manufacturers and policymakers in Jakarta and beyond as they seek to promote the adoption of cleaner and more sustainable transportation options. Furthermore, this research contributes to a broader understanding of the dynamics of EV adoption in urban settings and calls for continued efforts to improve service quality, innovation and customer satisfaction in the EV industry.